Strategi Media Cetak Dalam Mempertahankan Eksistensi Surat Kabar Di Era Digital: Studi Komparatif Harian Analisa, Harian Waspada, Dan Harian Sumut Pos - Siti Asyaroh; Irma Yusriani Simamora (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2025)
The development of technology, especially the internet, has made it easier to access information quickly. The internet is the main means to find all needs, both primary, secondary, and tertiary. Through websites, news apps, and social media, people can get information in seconds, allowing them to stay up-to-date with the latest developments in various fields. The shift in access to information from print to online media has occurred along with the advancement of digital technology, making people prefer information that is fast, practical, and easily accessible through the internet. This phenomenon is a challenge for print media in maintaining their existence, especially in producing newspapers. The decline in the number of prints continues to be experienced by various print media. Therefore, print media massively creates strategies to survive in the era of digitalization, starting from convergence, content innovation, managing advertising strategies, to distribution. This research is a comparative study between the media of Analisa Daily, Waspada Daily, and Sumut Pos Daily using qualitative methods. Data collection uses interview, observation, and documentation techniques.